Alternative Functional Forms and Errors of Pseudo Data Estimation - Maddala, G. S.; Roberts, R. Blaine (The Review of Economics and Statistics, 1980)
7 The F-statistic for the first test is F(4,107) = 0.50 while for the second test it is F(4,11 1) = 0.81. Both of these values are well below the critical-F at conventional levels of significance. 8 Further experimentation showed that one additional parameter could be eliminated by, for example, disposing of the last join point (setting d2 = 0.). However, since the purpose here was simply to show that fewer than 12 parameters are required, the equation has been left in the present form.